Role of high sensitivity C- reactive protein as a marker of inflammation and its prognostic significance in chronic kidney disease patients - Khunte, Sanjeev Kumar; Kumar, Jitendra; Khunte, Prakash (International Journal of Advances in Medicine, 2019)
Background: Chronic kidney disease (CKD) is a clinical syndrome due to irreversible renal dysfunction leading to excretory, metabolic and synthetic failure culminating into accumulation of non-protein nitrogenous substances and present with various clinical manifestations. Elevated circulating concentrations of CRP are a common phenomenon in ESRD patients. The prevalence and magnitude of inﬂammation increases as renal function declines. Methods: The current cross-sectional observation study was conducted in Rajendra institute of medical sciences, Ranchi during study period October 2015 to September 2017 on admitted patients with chronic kidney disease. 90 patients of different age groups between 16-75 years were enrolled in the study. Samples were selected by using simple random sampling method. Informed consent was obtained from all the patients. Results: 85.6% of the patients studied were males and 14.4% of the patients were females. Most cases of CKD were associated with hypertension (77.8%) out of which there were 62 males and 8 females, followed by DM (25.5%) where there were 20 males and 3 females. 44.4% cases had an elevated level of hs-CRP (more than 3 mg/L) while 55.6% patients had hs-CRP below 3 mg/l. Out of 40 high hs-CRP patients, 35 were male and 5 were female. Patients with elevated creatinine level had significant high hs-CRP level. Conclusions: Chronic kidney diseases, Cardiovascular disease, HS-CRP, Inflammation